Long Distance Broadband Fiber Optical Beamforming Over 120 km - Jichen Qiu (IEEE, 2021)
With the development of the space exploration and satellite communications, the data transmission at broadband and long distance are in increasing demand. To enhance the signal transmission capability from the satellite to the earth over deep space, multiple radars from distributed ground stations at cooperative mode might be a promising solution. Broadband beamforming with high efficiency over long distance fiber optic transmission links is investigated in the paper. To achieve phase stable transmission for broadband signal, fast active optical compensation is adopted by phase locking each fiber optic link with a separate wavelength to discriminate the time jitter induced phase variation. By matching the time delays between the different channels, the signal-noise ratio (SNR) of the beamformed broadband signal is improved significantly. In the experiment, a root mean square (RMS) of time delay variations of 0.86 ps and Allan deviation of $1.74× 10 ^{-13}$ for the carrier transmission in the phase locked fiber link over 120 km is achieved, and broadband fiber optical beamforming with data rate over 2 Gbit/s is successfully demonstrated.